Absorption of Vocational High Schools Department of Hospitality in the Field of Housekeeping Fresh Graduates at Four Star Hotels in the City of Bukittinggi - Hodril Hodril; Dasep Suryanto (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
The aim of this study is to determine whether fresh graduates of vocational higher education who major in hospitality need opportunities to work in four-star hotels in Bukittinggi, (2) determining the competence of the workforce for SMK graduates majoring in Hospitality to be accepted into four-star hotels in Bukittinggi City as workers, (3) determining the absorption rate for SMK graduates majoring in Hospitality in four-star hotels in Bukittinggi. The research used qualitative approach using the Exploration method. This research was conducted at the Grand Rocky Hotel and the Novotel Hotel, which are specialized in housekeeping. The number of focuses on hotels to be researched will be grouped only for employees related to the Recruitment and Housekeeping Departmen HR Manager and Executive Housekeeper. The results showed that based on their experience in recruiting prospective employees, it was found that SMK graduates were less diligent, less honest and less disciplined, this was evidenced by their mediocre quality of work, arriving late and leaving early, if given the responsibility to carry out tasks frequently, so that the work is not running well and not on time. Based on the results of interviews, observations and data documentation, an employee for housekeeping must (1) be honest in behavior and speech, admit the mistakes made and able to communicate well, (2) diligent, work seriously, taking high initiative, (3) discipline and responsible. Thus, students majoring in hospitality basically have many job opportunities, but their successful is depend on their performance during their internship period of approximately 4-6 months. Moreover, teachers must instill a diligent, honest, and disciplined attitude in the learning process because the ability to work in housekeeping is not enough to secure a job.